Women, Environment and Marketing: What Drives Green Purchase Intention of Cloth Menstrual Pads Among Generation Z - Andi Muhammad Sadat; Rachela Putri Hanasti; Nilnal Muna; Annisa Lutfia; Wisuwat Wannamakok (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study investigates the influence of environmental knowledge, green advertising, and environmental concern on green purchase intention toward cloth menstrual pad products, with attitude toward green products serving as a mediating variable and sustainability awareness functioning as a moderating variable.Methodology: Data were collected through an online survey of 421 Generation Z women residing in major Indonesian cities, namely Jakarta, Bandung, Surabaya, Medan, and Makassar, and analyzed using SmartPLS 4.Finding: The results reveal that environmental knowledge, green advertising, and environmental concern exert significant positive effects on attitudes toward green products, which subsequently enhance green purchase intention. Notably, environmental knowledge demonstrates a negative direct effect on purchase intention, while sustainability awareness fails to moderate the proposed relationships.Conclusion: These findings offer valuable insights for manufacturers, marketers, policymakers, and environmental organizations seeking to foster green purchase intention, particularly for sustainable products such as cloth menstrual pads